Application of indigenous Saccharomycopsis fibuligera for light-flavor Baijiu fermentation: Changes of microbial community and flavor metabolism - Jie Tang; Bin Lin; Yimin Shan; Gang Zhang; Liping Zhu; Wei Jiang; Qun Li; Lei Zhang; Shengzhi Yang; Qiang Yang; Shenxi Chen; Hai Du (Current Research in Food Science)
Ethyl acetate, a characteristic flavor compound in light-flavor Baijiu (LFB), plays a pivotal role in defining its sensory profile. Insufficient concentrations in fermented grains may diminish the quality of Baijiu. Indigenous microbial bioaugmentation has proven effective in improving Baijiu quality by reshaping microbial community and modulating flavor metabolism within fermentation ecosystems. This study investigated the effects of Jiuqu fortified with an indigenous Saccharomycopsis fibuligera Y162 on the microbial community, physicochemical parameters, and volatile compound profiles throughout the fermentation of LFB. Results demonstrated a significant increase in ethyl acetate content in both original Baijiu and fermented grains, alongside pronounced fungal community restructuring. PacBio single-molecule real-time (SMRT) sequencing analysis showed that Lactobacillus helveticus, Rhizopus sp., Saccharomyces cerevisiae, and Issatchenkia orientalis became the dominant species at the end of fermentation. Correlation network analysis revealed that ethyl acetate was significantly related (P < 0.05, |ρ| > 0.7) to the I. orientalis and Rhizopus sp. (the main fungal biomarkers), which was driven by the functional S. fibuligera. Mantel test further highlighted acidity, temperature, and moisture as critical environmental factors influencing the microbial community (P < 0.05, |ρ| > 0.7). To summarize, biofortification with S. fibuligera exhibited positive effects in enhancing typical flavor metabolites by influencing fungal community structure in LFB. These findings imply that the indigenous strains have great application potential in improving the quality of Baijiu.